The Metaanalysis of the Analgesic Effect of Electroencephalographic Neurofeedback for People with Chronic Pain - Elvina Zuhir; Desmawita Lestari; Reza Wahyudi; Aisya Raehan Fadhillah (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Chronic pain represents a major global health burden and often remains resistant to conventional pharmacological treatment, prompting the exploration of alternative therapeutic strategies. Electroencephalographic (EEG) neurofeedback has emerged as a non-invasive neuromodulatory intervention that enables patients to self-regulate brain activity and potentially alleviate persistent pain symptoms. This systematic review addresses the research problem of inconsistent evidence regarding the clinical efficacy and underlying mechanisms of EEG-based neurofeedback for chronic pain management in adults. A comprehensive analysis of 80 studies involving adults with chronic pain lasting at least three months was conducted, examining neurofeedback protocols, clinical pain outcomes, neurophysiological changes, secondary benefits, and methodological quality. Findings revealed heterogeneous results, with several studies reporting statistically significant and clinically meaningful pain reduction, particularly in conditions such as chemotherapy-induced neuropathy, fibromyalgia, and chronic back pain. Observed neurophysiological changes, including increased alpha power and modified connectivity in pain-related brain regions, were sometimes associated with clinical improvement, alongside reported benefits in sleep quality, mood, and overall well-being. However, evidence from sham-controlled randomized trials showed no significant differences between intervention and control groups, highlighting methodological limitations and challenges in blinding procedures. The review concludes that EEG neurofeedback is a safe and feasible intervention with potential therapeutic value for chronic pain, although current evidence remains inconsistent. The novelty of this study lies in its integrative evaluation of clinical outcomes, neurophysiological mechanisms, and protocol-specific effects, while emphasizing the need for personalized approaches, biomarker identification, and rigorous experimental designs to clarify efficacy and optimize treatment implementation.